1899 Tenn. Session Laws 780 - (:unkn) unknown (My University, 1899)
Provided however, That it shall be lawful for any person to hunt quail or partridges in said counties with a gun, between the first day of November and the first day of January of each year. But it is further provided, that it shall not be lawful to hunt upon the inclosed lands of another with a gun, as above mentioned, until written permission is first obtained from the owner or owners of such inclosed lands.
Keywords: TRANSFER